(untitled) (Research, Society and Development, 2019)
Action research is a social research modality that can collaborate with several research models. This article aims to discuss this methodological strategy and its possibilities of use as a pedagogical and scientific tool in education research. The paper analyzes the publications of the Brazilian Journal of Education, from 2016 to 2018, which use action research as a methodological procedure. The article is based on Thiollent’s (2005) research-action conceptions, in addition to the contribution of Moreira (2011) and Tripp (2005) and Minayo’s ideas of knowledge construction (2014). As a methodology, we used bibliographical research on the topic and documental research, through the survey of the productions in the editions of the Journal in the period under study, to identify the published works that effectively used the action research and informed this procedure. The research resulted in five productions that used the methodology in question, of a total of one hundred and forty three published articles, pointing out some difficulties of operationalization and execution of researches with this formatting. However, despite the implementation challenges, action research presents itself as a methodology with significant contributions to improve the quality of research in education.